The Ambiguity of NU's Digital Preaching in Identity Politics / Ambiguitas Dakwah Digital NU dalam Politik Identitas - titi, sitti ansoriah; Khotimah, Khusnul (Alhadharah: Jurnal Ilmu Dakwah, 2025)
This study discusses the ambiguity of Nahdlatul Ulama (NU) digital da'wah in facing religious populism and identity politics with a focus on NU's online media platform. This study was conducted because of the increasing strategic role of digital media in shaping religious and political public opinion in Indonesia, as well as NU's position as a representation of moderate Islam. The research approach used is qualitative with Van Dijk's critical discourse analysis method. This method is used to analyze the content of articles in NU Online related to moderation, religious identity, and populism. The results show that there is ambiguity in NU Online articles. Three main ambiguities are indicated by the results of the study: the narrative of moderation and exclusive nationalism, the paradox of rejecting identity politics, and the deradicalization debate that tends to define moderate Islam in a limited way. The results show that NU Online is not only a da'wah medium but also an arena for symbolic battles to maintain NU's hegemonic position in the landscape of identity politics in Indonesia. This study enhances our understanding of how mainstream religious media create ideologically laden da'wah narratives. In addition, this study shows how important it is to think critically when responding to digital da'wah messages in the era of religious populism.